High Prevalence of Post-stroke Anxiety in Elderly Patients Following COVID-19 Outbreak - Yao, Meiling; Li, Hongjie; Luo, Ying; Li, Ling; Yu, Jian (Frontiers in Psychiatry, 2021)
Abstract Objective: Post-Stroke Anxiety (PSA) is a common affective disorder in patients with ischemic stroke. The elderly are more susceptible to mental health issues, however, few studies have focused on PSA in elderly patients, especially in the context of COVID-19, causing a profound impact on the mental health of general people. The present study was to assess the prevalence and risk factors of PSA in elderly patients following COVID-19 outbreak. Methods: We retrospectively analyzed 206 elderly inpatients with newly diagnosed acute ischemic stroke in the Frist Affiliated Hospital, Sun Yat-sen University, from January 2020 to December 2020. Patients were categorized into the PSA group and the non-PSA group based on the scores Hamilton Anxiety Scale (HAMA) evaluated at admission (within one week after stroke onset). Meanwhile, demographic and clinical data, mental state by Mini-Mental State Examination (MMSE), stroke severity and outcome by National Institutes of Health Stroke Scale (NIHSS) and modified Rankin Scale (mRS), were compared between the two groups, respectively. Univariate analysis and binary logistic regression analysis were used to analyze risk factors associated with PSA. We determine the cutoff scores for significant predictors of PSA using the area under the curve (AUC) and receiver operating characteristic (ROC). Results: Of the 206 stroke patients, 62 (30.1%) developed anxiety. Binary logistic regression analysis showed that high NIHSS scores [adjusted odd ratio (aOR): 1.155, 95% confidence interval (CI):1.036-1.288, P=0.010] and single status (being divorced or widowed) [adjusted odd ratio (aOR): 2.884, 95% confidence interval (CI):1.089-7.639, P=0.033] were independent risk factors for PSA, as was a low MMSE score [adjusted odd ratio (aOR):0.932, 95% confidence interval (CI):0.879-0.986, P=0.017]. Cutoff threshold for the NIHSS scores was 3.5 points with an AUC of 0.64. Conclusion: Our results showed a high incidence of PSA in elderly patients after the COVID-19 outbreak. Being single (divorced or widowed), higher NIHSS scores and lower MMSE scores were the independent risk factors for PSA.